Iron phthalocyanine-sensitized magnetic catalysts for BPA photodegradation - Neamtu, Mariana (Sci Rep, 2020)
The catalytic behavior of iron phthalocyanine (FePc)-sensitized magnetic nanocatalysts was evaluated for their application in the oxidative treatment of Bisphenol A (BPA) under mild environmental conditions. Two types of FePc (Fe(II)Pc and Fe(III)Pc), which are highly photosensitive compounds, were immobilized on the surface of functionalized magnetite. The nanomaterials were characterized by high resolution transmission electron microscopy (HR-TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analyses (TGA). The generation of singlet oxygen by nanomaterials was also investigated. In the presence of UVA light exposure (365 nm) and 15 mM H(2)O(2), the M@Fe(III)Pc photocatalyst gave the best results; for a catalyst concentration of 2.0 g L (− 1), around 60% BPA was removed after 120 min of reaction. These experimental conditions were further tested under natural solar light exposure, for which also M@Fe(III)Pc exhibited enhanced oxidative catalytic activity, being able to remove 83% of BPA in solution. The water samples were less cytotoxic after treatment, this being confirmed by the MCF-7 cell viability assay.